Metals in sediments: bioavailability and toxicity in a tropical reservoir used for public water supply - Cardoso-Silva, Sheila [UNESP]; Da Silva, Daniel Clemente Vieira Rego; Lage, Fernanda; de Paiva, Teresa Cristina Brazil; Moschini-Carlos, Viviane [UNESP]; Rosa, André Henrique [UNESP]; Pompêo, Marcelo (Springer Nature, 2016)
Sediments may be a repository of contaminants in freshwater ecosystems. One way to assess the quality of this compartment, in terms of potentially bioavailable metals, is by the analysis of acid-volatile sulfide (AVS) and simultaneously extracted metals (SEM). In order to investigate the bioavailability, toxicity, and compartmentalization of different metals (Cd, Cr, Cu, Ni, Pb, Zn), sampling of surface sediments was performed at nine stations along the Paiva Castro reservoir (São Paulo, Brazil). The metals were analyzed using atomic absorption spectroscopy. Sediment organic matter (OM), organic carbon (OC), and grain size were also measured. The parameters pH, EH, temperature, and dissolved oxygen were determined at the sediment-water interface. Chronic and acute toxicological tests were performed with sediments from the area where water was extracted for the public water supply. Low levels of OM, associated with loss of stratification in the water column, explained the relatively low AVS values. The molar ratio ∑[SEM]−[AVS]/fOC was less than 130 mmol/kg−1 for all the sampling stations, indicating that the metals were not bioavailable. With the exception of Cd, metal levels were in accordance with background concentrations and the threshold effect level (TEL) established by the Canadian Council of Ministers of the Environment. The ecotoxicological tests confirmed the absence of toxic effects to biota. Application of principal component analysis indicated the presence of four compartments along the reservoir: (1) a riverine zone, potentially threatened by contamination with Cd; (2) an intermediate zone; (3) a limnic area; and (4) the area where water was taken for the public water supply.
Keywords: Contamination; Metal; Sediment; Spatial heterogeneity; Toxicity